PERAN RANCANGAN INTERVENSI DENGAN PENDEKATAN ART THERAPY TERHADAP BODY IMAGE DISSATISFACTION PADA PEREMPUAN DEWASA MUDA - Vera Ignatia Prawono (Universitas Bunda Mulia, 2015)
People perception toward their physical appearance or also known as body image has already been a great issue for long, especially in women. This issue appears whenever everyone finds the discrepancies between the real body and the ideal body image. The ideal body image is influenced strongly by the mass media at that moment. Nowadays, the ideal physical appearance for women based on media’s opinion is skinny body. If a woman finds her body doesn’t meet the ideal figure, then the body dissatisfaction will appear. Body dissatisfaction is related directly to lower body image satisfaction. Lower body image satisfaction (measured by MBSRQ) without any treatment will lead to eating disorder soon. Thus, it becomes urgent to treat women with body dissatisfaction to prevent those pathological areas. Treatment for women with body dissatisfaction is aimed to increase their body image satisfaction. The core of this treatment is to reconstruct the irrational thoughts of these women related to their body image. This treatment will use the approach of art therapy and will be given to five participants. All participants are women. Unlike the other approaches of therapy, art therapy doesn’t use too much verbal words as the main technique. Art therapy uses the art or creativity as the media to express the thoughts or feelings of clients. The results of this research show that the approach of art therapy is success in increasing the body image satisfaction in women with body dissatisfaction. Furthermore, the success of this intervention is varying between one participant and another. The personality factor is used to enrich the discussion of the result and also to analyze the difference of success quality in five participants. Keywords: body image dissatisfaction, art therapy, women